Cardanol-based benzoxazine-terminated graphene oxide-reinforced fluorinated benzoxazine hybrid composites for low K applications. Issue 8 (2nd August 2020) - Kurinchyselvan, S.; Chandramohan, A.; Hariharan, A.; Gomathipriya, P.; Alagar, M.
ABSTRACT: A novel fluorinated benzoxazine was prepared from bisphenol-AF, aniline and paraformaldehyde and was characterized by 1 H NMR, 19 F NMR and FTIR. A benzoxazine-functionalized silane-coupling agent was synthesized using renewable resource cardanol, paraformaldehyde and aminopropyltriethoxysilane (APTES). Cardanol benzoxazine-functionalized graphene oxide (GO-C-aps)-reinforced fluorinated benzoxazine (BAF-a) hybrid composites poly(GO-BAF-a) have been developed through the facile one step copolymerization route. XRD and SEM analyses were used to ascertain the morphology of the composite materials developed. Data obtained from thermal, dielectric and surface studies infer that the hybrid cardanol-based benzoxazine composites possess the enhanced thermal stability, improved hydrophobic behaviour with lower value of dielectric constant according to the weight percentage concentration of functionalized graphene oxide than those of neat benzoxazine matrix. The hybrid cardanol benzoxazine composites developed in the present work can find application in the form of coatings, sealants and adhesives for interlayer low k dielectric insulation applications in microelectronics industries. Graphical abstract: